PERAN MEDIASI KEPUASAN KERJA ATAS PENGARUH GAYA KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI (Studi kasus pada Kantor Dinas Pendidikan dan Kebudayaan Kota Probolinggo) - Santi Rahayu; Muryati, Muryati (Bajang Institute, 2025)
The objective to be achieved in this study is to find out empirical evidence about the mediating role of job satisfaction on the influence of leadership style and organizational climate on employee performance. This study uses a quantitative approach with the type of research used is explanatory research. The study was conducted at the Office of Education and Culture of Probolinggo City. The population is all Civil Servants at the Office of Education and Culture of Probolinggo City, totaling 56 people. The researcher selected the sample using a saturated sampling technique because the population is relatively small. The data analysis technique used is partial least square- structural equation modeling using smart-pls software. The results of the study show that leadership style can improve employee performance. Leadership style can improve job satisfaction. Organizational climate is not able to improve employee performance. Organizational climate is able to improve job satisfaction. Job satisfaction is able to improve employee performance. Job satisfaction plays a role in mediating some of the influence of leadership style on employee performance. Job satisfaction plays a role in perfectly mediating the influence of organizational climate on employee performance